PENINGKATAN HASIL BELAJAR IPA MELALUI MODEL PEMBELAJARAN PROBLEM BASED INTRODUCTION PADA SISWA KELAS II SD INPRES BONTOCINIAYO - ., Muliati (Inspiratif Pendidikan, 2018)
This research is a classroom action research that aims to improve the learning outcomes of class II SDI Bontociniayo through the use of the Problem Based Introduction (PBI) method. The subject of this study was class II SDI Bontociniayo with 26 students consisting of 15 female students and 11 male students.This research was conducted in two cycles, namely the first cycle was carried out 2 times and the second cycle was also conducted two meetings, which were conducted for 2 months. The result is an increase in student learning outcomes through the Problem Based Introduction (PBI) method is (i) The level of learning outcomes of class II SDI Bontociniayo in the first cycle included in the high category with an average value of 68.2 while in the second cycle progressed with the category very high with an average value of 77.4, (ii) There is an increase in the learning outcomes of class II SDI Bontociniayo through the application of the Problem Based Introduction (PBI) method, both qualitatively and quantitatively. This can be seen in the table and explanation in the attachment, in the first cycle and second cycle of each action starting from action I to action II.In connection with the above results, the learning model is considered to be quite effective in teaching especially in the field of science studies, because it can improve student learning outcomes both in doing their assignments in school and providing opportunities for students to always try (experiment) in each activity learning so that they can be more motivated to achieve maximum achievement.